2022
DOI: 10.20945/2359-3997000000525
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 process on patients with endocrinological disease in a pandemic hospital: What happened to the others?

Abstract: Objective: To evaluate the effects of the pandemic process on those with an endocrinological disease that will require close follow-up from the last visit before the pandemic. Materials and methods: Patients of 3,903 with thyroid, calcium-bone metabolism, adrenal gland, pituitary diseases, and neuroendocrine tumor (NET) were retrospectively scanned. The remaining 855 (656 females and 199 males) patients with active disease or who still needed multidisciplinary approaches were included. The number of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Of note, a study analyzing medical deprivation rate in patients with endocrine disease during pandemic showed that individuals with AD had the lowest rate (of 0%) as opposed, for instance, with high rates for differentiated thyroid carcinoma (of 89%). 148 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, a study analyzing medical deprivation rate in patients with endocrine disease during pandemic showed that individuals with AD had the lowest rate (of 0%) as opposed, for instance, with high rates for differentiated thyroid carcinoma (of 89%). 148 …”
Section: Discussionmentioning
confidence: 99%
“…New data showed that patients with AI did not suffer from new restrictions for a certain period of time as opposed to other endocrine patients and that the first two doses of vaccines required a higher glucocorticoid dose in less than one out of 10 individuals. 148 , 149 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation